Maternal Behavior Regarding Nutrition and Eating Culture of Children Under Five in the Stunting Locus Area, Nusa Tenggara Timur - Picauly, Intje (Journal of Maternal and Child Health, 2024)
Background: Stunting has become a major nutritional problem for children under five in Indonesia. Since 2007 until now, the problem of stunting has been detected in Flobamora, including Rote Ndao Regency. The results of the weighing operation in 2023 reported that the prevalence of stunting in NTT province was 21.7%. Measurement data shows that in 2023 there will be 414 babies born, with 38 children experiencing stunting as measured using the baby's birth length. Mother's behavior regarding nutrition and culture of child eating patterns from the time the child is in the womb until the age of under five years plays an important role in shaping the quality of human resources, including preventing the problem of malnutrition, especially stunting. This study aimed to determine the relationship between maternal behavioral factors regarding nutrition and the eating culture of children under five in the stunting locus area, East Nusa Tenggara Province. Subjects and Method: This was a cross sectional study carried out in Mokdale Village, Lobalain District, Rote Ndao Regency, East Nusa Tenggara, Indonesia, from June to August 2023. A sample of 44 children aged 12 to 36 months, consisted of 22 stunted children and 22 normal height children was selected for this study. The dependent variable was stunting. The independent variables were maternal behavior, knowledge, attitude, and feeding practice, child’s eating behavior. The data were analyzed using Chi-square. Results: The incidence of stunting in children increased with maternal behavior regarding poor nutrition (OR = 2.72; 95% CI= 1.25 to 4.19; p= 0.001); maternal knowledge about poor nutrition (OR= 1.13; 95% CI= -1.06 to 2.37; p = 0.060); attitude = mother regarding poor nutrition (OR = 1.74; 95% CI=0.44 to 3.03; p =0.001); maternal actions regarding malnutrition (OR = 3.07; 95% CI = 1.50 to 4.64; p=0.001); and poor eating culture of children under five (OR= 3.03; 95% CI= 0.12 to 3.57; p= 0.001), and these result were statistically significant Conclusion: Maternal behavioral factors regarding good nutrition and good eating culture are closely related and can reduce the chances of problems with the nutritional status of toddlers in the stunting locus area, Lobalain District, Rote Ndao Regency, East Nusa Tenggara Province.